2021
DOI: 10.1128/jcm.00527-21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cell-Based and Surrogate SARS-CoV-2 Neutralization Assays

Abstract: Determinants of protective immunity against SARS-CoV-2 infection require the development of well-standardized, reproducible antibody assays. This need has led to the emergence of a variety of neutralization assays. Head-to-head evaluation of different SARS-CoV-2 neutralization platforms could facilitate comparisons across studies and laboratories. Five neutralization assays were compared using forty plasma samples from convalescent individuals with mild-to-moderate COVID-19: four cell-based systems using eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 72 publications
(78 reference statements)
5
77
0
Order By: Relevance
“…Pseudo-typed and chimeric viruses have been used most frequently because it is simpler to introduce mutations into a plasmid encoding just the spike gene compared with using a clinical virus isolate or a recombinant virus generated using a system that requires either multiple plasmids or bacterial or yeast artificial chromosomes 119,120 . Although the results of neutralization experiments using pseudo-typed viruses, VSV-based chimeric viruses and full-length SARS-CoV-2 usually yield similar results 97,107,125,126 , full-length viruses are expected to be more reliable and can be studied in animal models 127 .…”
Section: In Vitro Selection and Neutralization Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudo-typed and chimeric viruses have been used most frequently because it is simpler to introduce mutations into a plasmid encoding just the spike gene compared with using a clinical virus isolate or a recombinant virus generated using a system that requires either multiple plasmids or bacterial or yeast artificial chromosomes 119,120 . Although the results of neutralization experiments using pseudo-typed viruses, VSV-based chimeric viruses and full-length SARS-CoV-2 usually yield similar results 97,107,125,126 , full-length viruses are expected to be more reliable and can be studied in animal models 127 .…”
Section: In Vitro Selection and Neutralization Experimentsmentioning
confidence: 99%
“…antibodies. In summarizing the results of neutralizing experiments, we have also pooled results obtained using pseudo-typed, chimeric and infectious viruses as the results of these assays are usually concordant 97,107,125,126 .…”
Section: Deep Mutational Scanningmentioning
confidence: 99%
“…In seeking to establish a CoP for COVID-19 vaccines, both Earle et al 11 and Khoury et al 12 initially showed only a weak relationship between efficacy and reported nAb or binding antibody (bAb) titers 11,12 . This poor association could be explained by the high variation observed between the selected assays used by different studies 17,18 . This variability was partially mitigated by calibrating the assays against panels of human convalescent sera (HCS) run within the same study.…”
Section: Clinical Data Support Nab As a Biomarker Of Protectionmentioning
confidence: 99%
“…Determinants of protective immunity against SARS-CoV-2 infection require the development of well-standardized, reproducible high-throughput antibody assays which can pinpoint people who are at a particular risk. They may also provide information on how often booster vaccinations might be needed and help in developing improved vaccines and immunotherapies [177][178][179]. Nevertheless, there are significant concerns about only using the antibody response in coronavirus infections as a sole metric of protective immunity [180].…”
Section: What Are Strong and Measurable Correlations Between Protection And Disease?mentioning
confidence: 99%